Rapidly measured indicators of recreational water quality and swimming-associated illness at marine beaches: a prospective cohort study - Love David; Rankin Clifford C; Wymer Larry; Beach Michael; Chern Eunice; Haugland Richard; Brenner Kristen P; Sams Elizabeth; Wade Timothy J; Li Quanlin; Noble Rachel; Dufour Alfred P (BMC, 2010)
Abstract Introduction In the United States and elsewhere, recreational water quality is monitored for fecal indicator bacteria to help prevent swimming-associated illnesses. Standard methods to measure these bacteria take at least 24 hours to obtain results. Molecular approaches such as quantitative polymerase chain reaction (qPCR) can estimate these bacteria faster, in under 3 hours. Previously, we demonstrated that measurements of the fecal indicator bacteria Enterococcus using qPCR were associated with gastrointestinal (GI) illness among swimmers at freshwater beaches. In this paper, we report on results from three marine beach sites. Methods We interviewed beach-goers and collected water samples at marine beaches affected by treated sewage discharges in Mississippi in 2005, and Rhode Island and Alabama in 2007. Ten to twelve days later, we obtained information about gastrointestinal, respiratory, eye, ear and skin symptoms by telephone. We tested water samples for fecal indicator organisms using qPCR and other methods. Results We enrolled 6,350 beach-goers. The occurrence of GI illness among swimmers was associated with a log10-increase in exposure to qPCR-determined estimates of fecal indicator organisms in the genus Enterococcus (AOR = 2.6, 95% CI 1.3-5.1) and order Bacteroidales (AOR = 1.9, 95% CI 1.3-2.9). Estimates of organisms related to Clostridium perfringens and a subgroup of organisms in the genus Bacteroides were also determined by qPCR in 2007, as was F+ coliphage, but relationships between these indicators and illness were not statistically significant. Conclusions This study provides the first evidence of a relationship between gastrointestinal illness and estimates of fecal indicator organisms determined by qPCR at marine beaches.